Nitrogen nutrition for lettuce effects of N-carriers and nitrification inhibition - Pereira, Newton N.C.; Fernandes, Manlio S.; Almeida, Dejair L. de (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was carried out to study the effects of N-sources (urea, nitrocalcium, ammonium sulphate, chicken dung and biodigestor efluent) with (CNS) and without (SNS) a nitrification inhibitor (Nitrapyrin) on the dry weight and N-uptake of lettuce (Lactuca sativa, L.). The nitrification inhibitor per se had no negative effect on growth of lettuce. However, nitrification inhibitor + urea resulted in a sharp decrease in plant growth rates. The application of nitrocalcium and chicken dung + NS also resulted in decreases of lettuce dry weight. The highest rate of dry weight accumulation was induced by chicken dung - SNS. On the other hand, biodigestor effluent was shown to be a very poor source of N. The chicken dung treatment resulted in NO3- accumulation in lettuce at levels potencially harzardous to human health. It is proved that under the present cropping system, an excess of N is used by lettuce growers in Rio de Janeiro.